A Tool for Improving the Longitudinal Imaging Characterization for Neuro-Oncology Cases - Taira, Ricky K. (American Medical Informatics Association, 2008)
We describe the development of a prototype tool for the construction of longitudinal cases studies that can be used for teaching files, construction of clinical databases, and for patient education. The test domain is neuro-oncology. The features of the tool include: 1) natural language processing tools to assist structuring report information; 2) integration of imaging data; 3) integration of drug information; 4) target data model that includes the dimensions of space, time, existence, and causality; 5) user interface that provides three levels of information including overview, filtered summarization, and details on demand. The results of this preliminary work include a full prototype for neuro-oncology patients that allow users an efficient means for scanning a patient’s imaging and support data.